Current insights into thrombotic microangiopathies: Thrombotic thrombocytopenic purpura and pregnancy. Issue 135 (February 2015) - von Auer, Charis; von Krogh, Anne-Sophie; Kremer Hovinga, Johanna A.; Lämmle, Bernhard
ABSTRACT: The complex relation between thrombotic thrombocytopenic purpura (TTP) and pregnancy is concisely reviewed. Pregnancy is a very strong trigger for acute disease manifestation in patients with hereditary TTP caused by double heterozygous or homozygous mutations of ADAMTS13 (A D isintegrinA ndM etalloprotease withT hromboS pondin type 1 domains, no. 13). In several affected women disease onset during their first pregnancy leads to the diagnosis of hereditary TTP. Without plasma treatment mother and especially fetus are at high risk of dying. The relapse risk during a next pregnancy is almost 100% but regular plasma transfusion starting in early pregnancy will prevent acute TTP flare-up and may result in successful pregnancy outcome. Pregnancy may also constitute a mild risk factor for the onset of acute acquired TTP caused by autoantibody-mediated severe ADAMTS13 deficiency. Women having survived acute acquired TTP may not be at very high risk of TTP relapse during an ensuing next pregnancy but seem to have an elevated risk of preeclampsia. Monitoring of ADAMTS13 activity and inhibitor titre during pregnancy may help to guide management and to avoid disease recurrence. Finally, TTP needs to be distinguished from the much more frequent hypertensive pregnancy complications, preeclampsia and especially HELLP (H emolysis, E levatedL iver Enzymes, L owP latelet count) syndrome.